Protective efficacy of oral whole-cell/recombinant-B-subunit cholera vaccine in Peruvian military recruits - Sanchez, J.L; Vasquez, B; Begue, R.E; Meza, R; Castellares, G; Cabezas, C; Watts, D.M; Svennerholm, A-M; Sadoff, J.C; Taylor, D.N (The Lancet (British edition), 1994)
Summary The cholera epidemic in South America has reinforced the need for safe and effective oral vaccines. In a randomised, double-blind, placebo-controlled efficacy trial among 1563 Peruvian military recruits we have investigated the protective efficacy of an oral inactivated whole-cell/recombinant-B-subunit (WC/rBS) cholera vaccine. Participants were given two oral doses of cholera vaccine or Escherichia coli K12 placebo, with an interval of 7-14 days. 1426 (91%) subjects received the two prescribed doses and were followed up for a mean of 18 weeks (median 21 weeks). After vaccination, Vibrio cholerae 01 El Tor Ogawa was isolated from 17 subjects with diarrhoea. 16 of the cholera cases occurred 2 weeks or longer after the second dose of vaccine (14 placebo recipients, 2 vaccinees). We also detected 14 symptomless infections (11 [7 placebo recipients, 4 vaccinees]) 2 weeks or longer after the second dose. The vaccine had significant protective efficacy against cholera (86% [95% Cl 37-97], p<0·01) but not against symptomless infection (42% [-96 to 85]). All cholera cases were in people of blood group O, who made up 76% of the study population (p<0·01). Two doses of WC/rBS vaccine, given 1 to 2 weeks apart, provide rapid, short-term protection against symptomatic cholera in adult South Americans, who are predominantly of blood group O. Long-term efficacy studies in Peruvian adults and children are under way.